Non-surgical intervention for palliative treatment in Late-presentation Tetralogy of Fallot (TOF): Is there any hope? - Siregar, Indah Pratiwi (The Indonesian Heart Association, 2024)
Background: Late congenital heart disease (CHD) in patients with tetralogy of Fallot (TOF). Due to the variable severity of defects in patients with TOF, late presentation of CHD may only be discovered beyond the neonatal period. Chronic polycythemia from TOF may increase the risk of hemorrhaging during surgery and patients with untreated TOF risk developing CHD-related pulmonary hypertension. Non-surgical transcatheter palliation in patients with TOF may be applied; however, the efficacy and safety of the method remained very scarce. Therefore, we report two cases of late-presenting TOF treated with non-surgical transcatheter palliation due to high perioperative risks for surgical repair of the defects. Case Illustration: A 41-year-old (Case 1) and 19-year-old man (Case 2) were admitted to the emergency room due to chief complaint of dyspnea and severe headache with previous history of hypoxic spell, respectively. Both patients had presented with signs of right ventricular hypertrophy and cardiomegaly from physical examination. Echocardiography had confirmed TOF in both cases. Non-surgical palliation for both cases were performed with right ventricular outflow tract (RVOT) stenting and balloon pulmonary valvuloplasty (BPV), respectively. Both patients had shown clinical and systolic function improvement after both interventions. Conclusion: Late-presentation TOF may present with major comorbidities that contraindicates definitive repair of the defects due to high perioperative risk. Palliative interventions in late-presentation TOF may be considered as a bridging procedure prior to the definitive repair to minimize the risk of complications from untreated TOF beyond neonatal period.